Determinants of Unemployment Duration for Men and Women in Turkey - Aysit Tansel; Mehmet Tasci (Turkish Economic Association, 2004)
There are few studies on unemployment duration in developing countries. This is the first study on duration aspect of unemployment in Turkey. We use the results of the Household Labor Force Surveys of 2000 and 2001 to construct a cross-section of durations of unemployment spells. We analyze the determinants of probability of leaving unemployment or the hazard rate. The effects of the personal and household characteristics and the local labor market conditions are examined. Non-Parametric and parametric estimation methods are used, controlling for the unobserved heterogeneity. Two alternative definitions of unemployment are considered. The analyses are carried out for men and women separately. Our results indicate that women are experiencing higher unemployment durations then men. Age has a negative and education has a positive effect on the hazard rate. The effect of the local unemployment rate is large and negative. Duration dependence of the exit rate from unemployment is different for men and women. For men, there is slight U-shaped duration dependence, while for women there is no duration dependence.
Keywords: J64; C41; J16; 330; Unemployment Duration; Duration Analysis; Gender; Turkey